Early formation of carbon monoxide in the Centaurus A supernova SN 2016adj. Issue 1 (18th August 2018) - Banerjee, D P K; Joshi, Vishal; Evans, A; Srivastava, Mudit; Ashok, N M; Gehrz, R D; Connelley, M S; Geballe, T R; Spyromilio, J; Rho, J; Roy, R
ABSTRACT: We present near-infrared spectroscopy of the NGC 5128 supernova SN 2016adj in the first two months following discovery. We report the detection of first-overtone carbon monoxide emission at ∼58.2 d after discovery, one of the earliest detections of CO in an erupting supernova. We model the CO emission to derive the CO mass, temperature, and velocity, assuming both pure 12 CO and a composition that includes 13 CO; the case for the latter is the isotopic analyses of meteoritic grains, which suggest that core-collapse supernovae can synthesize significant amounts of 13 C. Our models show that, while the CO data are adequately explained by pure 12 CO, they do not preclude the presence of 13 CO, to a limit of 12 C/ 13 C > 3, the first constraint on the 12 C/ 13 C ratio determined from near-infrared observations. We estimate the reddening to the object, and the effective temperature from the energy distribution at outburst. We discuss whether the ejecta of SN 2016adj may be carbon-rich, what the infrared data tell us about the classification of this supernova, and what implications the early formation of CO in supernovae may have for CO formation in supernovae in general.